Investigating Factors Influencing K-12 Teachers’ Intention to Integrate Mobile Devices in Teaching - Zhu, Sha; Qiu, Hongjing; Yang, Harrison Hao; Zhang, Yi (Blended Learning: Aligning Theory with Practices, 2016)
The purpose of this study was to explore the key factors influencing K-12 teachers’ intention of mobile devices integration in teaching. A structural model of the factors influencing teachers’ intention to integrate mobile devices in teaching was proposed based on an extensive literature review. Based on the proposed model, a survey was administered which included six categories: (1) Attitude and technology belief; (2) Mobile-based pedagogical knowledge; (3) Mobile device skills; (4) Institutional support; (5) Self-efficacy of mobile-based teaching; and (6) Intention to integrate mobile devices. Partial Least Squares (PLS) were employed to validate the proposed model and hypotheses, using the data collected from 22 primary school teachers via surveys. The results indicated that teachers’ attitude and technology belief, and self-efficacy of mobile-based teaching had significant impacts on their intention to integrate mobile devices in teaching. Meanwhile, teachers’ mobile device skills strongly influenced their self-efficacy of mobile-based teaching. Finally, the authors provided suggestions for teachers, school leaders, and researchers.